The impact of neutrophil extracellular traps induced by Pseudomonas aeruginosa on dendritic cells - Xiaotong LIU; Jin LUO; Jinling TANG; Yuting HUANG; Shihao YANG; Jinliang KONG (Guangxi Yike Daxue xuebao)
Objective To investigate the regulatory effects of neutrophil extracellular traps (NETs) induced by Pseudomonas aeruginosa (PAO1) on dendritic cells (DCs). Methods Human peripheral blood neutrophils were isolated in vitro and stimulated with phorbol myristate acetate (PMA) and PAO1 (at multiplicities of infection, MOI=1, 10, 100) to induce NET formation. The NET morphology was observed via immunofluorescence staining, and NET-DNA concentration was quantified using PicoGreen fluorescence assay. PAO1-induced NETs were co-cultured with DCs. Flow cytometry was used to detect the expression levels of co-stimulatory molecules (CD40, CD86, CD80) on DC surfaces, while reverse transcription-quantitative polymerase chain reaction (RTqPCR) and enzyme-linked immunosorbent assay (ELISA) were employed to measure the transcription and secretion levels of interleukin-1β (IL-1β), interleukin-12 (IL-12), and tumor necrosis factor-α (TNF-α). Results PAO1- induced NETs exhibited nuclear enlargement and filamentous connection structures. The concentration of NETDNA in the MOI=100 group was significantly higher than that in the MOI=1 group (P < 0.01). The release of NET-DNA first increased and then decreased from 1 to 3 hours, reaching a peak at 4 hours. PAO1-induced NETs significantly upregulated the expression of co-stimulatory molecules CD40, CD86, and CD80 on the surface of DCs (P < 0.001) and promoted the secretion of IL-1β, IL-12, and TNF-α (P < 0.01). Conclusion PAO1-induced NETs can promote the maturation and activation of DCs, and induce the secretion of pro-inflammatory cytokines IL-1β, IL-12, and TNF-α. This pro-inflammatory effect may have dual roles.